2022
DOI: 10.1186/s12985-022-01934-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of an indirect ELISA using a novel linear epitope at the C-terminal region of the VP2 protein to specifically detect antibodies against Senecavirus A

Abstract: Background Senecavirus A (SVA) is a pathogen that has recently caused porcine idiopathic vesicular disease (PIVD). The clinical signs are similar to those of foot-and-mouth disease, porcine vesicular disease, and vesicular stomatitis. Therefore, identification of SVA as a cause of PIVD is important to eliminate this emerging pathogen. Methods In this study, an indirect ELISA based on the VP2 epitope (VP2-epitp-ELISA) was developed to detect antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Furthermore, the C-terminal region of VP2 ( 271 GLRNRFTTGTDEEQ 284 ) was identified as a diagnostic target for testing SVA antibodies in pigs (Ma et al, 2022 ). In the present study, the minimal epitope 266 SPYFNGL 272 of the C-terminus of VP2 was identified accurately by the mAb 2C7, and two amino acids (Gly 271 and Leu 272 ) were found overlapping with previous study conducted by Ma et al Recently, the epitope 267 PYFNGLRNRFTTGT 280 was predicted and identified by bioinformatics-based computational prediction and the Pepscan approach (Ru et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the C-terminal region of VP2 ( 271 GLRNRFTTGTDEEQ 284 ) was identified as a diagnostic target for testing SVA antibodies in pigs (Ma et al, 2022 ). In the present study, the minimal epitope 266 SPYFNGL 272 of the C-terminus of VP2 was identified accurately by the mAb 2C7, and two amino acids (Gly 271 and Leu 272 ) were found overlapping with previous study conducted by Ma et al Recently, the epitope 267 PYFNGLRNRFTTGT 280 was predicted and identified by bioinformatics-based computational prediction and the Pepscan approach (Ru et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies, several B-cell epitopes (BCEs) of SVA VP2 were identified by bioinformatics prediction (Ru et al, 2023 ; Zhang et al, 2023 ), overlapping synthesis of polypeptides (Ma et al, 2022 ) and monoclonal antibodies (mAbs) (Fan et al, 2020 ; Wen et al, 2022 ). It has been confirmed that 153 QELNEE 158 is a conserved antigenic epitope of the VP2 protein and has virus-neutralizing activity (Wen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seroconversion against SVA in clinically affected and non-clinically affected sows at early stages of the outbreak and maternal SVA antibodies in offspring were detected by rVP1 ELISA [17]. Recently, an indirect ELISA based on the VP2 epitope (VP2-epitp-ELISA) was developed to detect antibodies directed against SVA, and no cross-reaction with positive serum antibodies occurred for other idiopathic vesicular diseases [18]. Although these ELISA methods were well characterized, none of them were extended to mass diagnostic programs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, few studies have clarified that the antigenic reactivity of SVA VP1 is not the most immunodominant. Recently, an indirect ELISA based on the VP2 epitope (VP2-epitp-ELISA) was developed to detect antibodies directed against SVA [18]. The method has not been utilized to process large numbers of samples in epidemiological surveillance and mass diagnostic programs.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms observed in pigs infected by SVA resemble those caused by vesicular stomatitis virus (VSV) and foot-and-mouth disease virus (FMDV), leading to difficulties in clinical differential diagnosis ( Schmitt, 2002 ; Knight-Jones et al., 2016 ). Currently, many methods such as PCR-based assays and ELISA have been established for the laboratory diagnosis of SVA ( Bracht et al., 2016 ; Feronato et al., 2018 ; Mu et al., 2020 ; Ma Z. et al., 2022 ; Yan et al., 2023 ). However, these methods are cumbersome, complex and time-consuming.…”
Section: Introductionmentioning
confidence: 99%